Trust and Transparency: Auditor Independence and Financial Statement Integrity through the Lens of Business Ethics - Dajtnicka, Erlina Widayanti; Salsabila Helwani, Zahwa; Wulandari, Dian (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
Auditor independence and business ethics are critical to ensuring the integrity of financial statements, which underpins stakeholder trust in financial reporting. This study investigates the impact of auditor independence on financial statement integrity and examines the moderating role of business ethics. Using panel data regression, the research analyzed data from 150 publicly listed companies in Indonesia between 2019 and 2022. The results reveal that auditor independence has a significant positive effect on financial statement integrity, and business ethics independently enhances financial reporting quality. However, the moderating effect of business ethics on the relationship between auditor independence and financial statement integrity was not statistically significant. These findings highlight the complementary but independent roles of auditor independence and business ethics. The study underscores the importance of fostering both regulatory compliance and ethical organizational climates to ensure transparent and reliable financial reporting. Limitations and suggestions for future research are discussed.